Methodology Applied by a Physician Assistant Program to Evaluate the New ARC-PA 5th Edition Diversity and Inclusion Standard. Issue 4 (December 2022) - Rolfs, Jenna; Nicholas, Joyce; Archambault, Mark E.; Schmidt, Eric
Abstract: Diversity and inclusion in higher education are a top priority for institutions. In 2020, the Accreditation Review Commission on Education for the Physician Assistant (ARC-PA), in its 5 th edition of the Accreditation Standards for Physician Assistant Education, implemented a standard specifically designed to require programs to demonstrate their commitment to diversity and inclusion. Through a protocol-driven methodology, consistent with the ARC-PA's 4 key elements of analysis, one PA program demonstrates and explains how it examines ongoing compliance with diversity and inclusion within their program.